2021
DOI: 10.1016/j.neuroimage.2021.118030
|View full text |Cite
|
Sign up to set email alerts
|

Decoding visual colour from scalp electroencephalography measurements

Abstract: Recent advances have made it possible to decode various aspects of visually presented stimuli from patterns of scalp EEG measurements. As of recently, such multivariate methods have been commonly used to decode visual-spatial features such as location, orientation, or spatial frequency. In the current study, we show that it is also possible to track visual colour processing by using Linear Discriminant Analysis on patterns of EEG activity. Building on other recent demonstrations, we show that colour decoding: … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 52 publications
6
26
0
Order By: Relevance
“…For each model, we calculated the correlation between the weights from each cue unit and the recurrent units (weights from an example model shown in Fig 4B). Consistent with other recent observations, we found that the models learnt opposing weight patterns for the two retro-cue inputs [11,23]. More specifically, the recurrent units that had positive connections weights with the first retro-cue unit had negative connection weights linking them with the other cue unit, and vice versa.…”
Section: Learning Dynamics and Connectivitysupporting
confidence: 90%
“…For each model, we calculated the correlation between the weights from each cue unit and the recurrent units (weights from an example model shown in Fig 4B). Consistent with other recent observations, we found that the models learnt opposing weight patterns for the two retro-cue inputs [11,23]. More specifically, the recurrent units that had positive connections weights with the first retro-cue unit had negative connection weights linking them with the other cue unit, and vice versa.…”
Section: Learning Dynamics and Connectivitysupporting
confidence: 90%
“…Data were further preprocessed. Magnitudes of magnetometers were approximately matched to gradiometers by multiplication (factor 20) and subjected to spatiotemporal decoding (code available at https://pypi.org/project/temp-dec/ ; as described previously, Wolff et al, 2017 , 2020 ; Hajonides et al, 2021 ). Data from all 306 MEG sensors across a sliding window of 30 time points (150 ms) were concatenated into a 9180-dimensional vector.…”
Section: Methodsmentioning
confidence: 99%
“…Data were further pre-processed, where magnitudes of magnetometers were approximately matched to gradiometers by multiplication (factor 20) and subjected to spatio-temporal decoding as described in (Hajonides, Nobre, van Ede, & Stokes, 2021;Wolff, Jochim, Akyürek, Buschman, & Stokes, 2020;Wolff, Jochim, Akyürek, & Stokes, 2017). Data from all 306 MEG sensors across a sliding window of 30 time points (150 ms) were concatenated into a vector.…”
Section: Lda Classificationmentioning
confidence: 99%